2008
DOI: 10.5367/000000008786440201
|View full text |Cite
|
Sign up to set email alerts
|

Demand-Driven Sustainable Tourism? A Choice Modelling Analysis

Abstract: This paper studies the preferences of tourists visiting Sardinia (Italy), using a choice modelling approach. The focus is on the evaluation of specific 'demand-enhancing effects' which, according to economic theory, provide a basis for implementing sustainable tourism policies. Multinomial logit estimates reveal that strong negative effects result from the congestion of tourist attractions and the transformation of coastal environments, though tourists clearly gain utility from the other components of a touris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…In taking account of the preferences of the environmentally conscious tourist segment, the service providers are required to invest in the adaptation and modernization of facilities to make them more ecological (Accinelli et al, 2007;Brau, 2008;Claude and Zaccour, 2009;Minciu et al, 2010). Ogonowska and Torre (2013a) propose a theoretical framework to model the influence of demand on the strategic choices made by a given accommodation provider.…”
Section: Sociological Foundations Of a Demand-driven Vertical Differementioning
confidence: 99%
See 1 more Smart Citation
“…In taking account of the preferences of the environmentally conscious tourist segment, the service providers are required to invest in the adaptation and modernization of facilities to make them more ecological (Accinelli et al, 2007;Brau, 2008;Claude and Zaccour, 2009;Minciu et al, 2010). Ogonowska and Torre (2013a) propose a theoretical framework to model the influence of demand on the strategic choices made by a given accommodation provider.…”
Section: Sociological Foundations Of a Demand-driven Vertical Differementioning
confidence: 99%
“…It is envisaged as leading to management of all resources in such a way, that economic, social and aesthetic needs can be fulfilled while maintaining cultural integrity, essential ecological processes, and biological diversity and life support systems." Thus, local authorities and administrations need to develop appropriate policies focused on environmental protection that incentivize market actors to implement ecologically responsible measures and amenities (Accinelli et al, 2007(Accinelli et al, , 2008Brau, 2008;Claude and Zaccour, 2009;Minciu et al, 2010;Rivera, 2002;Weaver, 2005).To smoothen the implementation of environmental policies, it will be necessary to educate the market actors (hotel management, tourism agents, tour operators, administration) as well as the local population in order to adapt perceptions to a new long-term vision of sustainable tourism development (Henry and Jackson, 1995;Jamal et al, 2011;Nita and Agheorghiesei, 2010).…”
Section: Introduction and Definition Of The Concept Of Competitivenessmentioning
confidence: 99%
“…Multiple authors note that cautionary management of natural resources can prove successful in ensuring optimal use of those resources but can also increase tourists' willingness to pay (Lanza and Pigliaru, 1995;Brau, 2008). This cautionary management contrasts with the way many destinations have developed their tourism industry as often the main goal of development has been to develop infrastructure, buildings and services, "whose construction often negatively affect the original features of the very natural resources that make a given area attractive as a tourist destination" [Brau, (2008), p.692].…”
Section: Stakeholder Theory and Willingness To Paymentioning
confidence: 99%
“…Too many tourism related business may move in and detract from the tourist landscape, degrade whatever comparative advantage they have and ultimately lead to slower growth of the tourism industry. In a stated preference choice modeling-based survey of tourism demand, Brau (2008) found that the risk of overcrowding was one of the most important features of destinations for prospective tourists, even more important than the variety of recreation opportunities available or the proximity of the main attraction.…”
Section: Reasons For An Increasing Disperion In Global Tourismmentioning
confidence: 99%